2008
DOI: 10.1016/j.dnarep.2008.03.020
|View full text |Cite
|
Sign up to set email alerts
|

Endogenous hSNM1B/Apollo interacts with TRF2 and stimulates ATM in response to ionizing radiation

Abstract: Human SNM1B/Apollo is involved in the cellular response to DNA-damage, however, its precise role is unknown. Recent reports have implicated hSNM1B in the protection of telomeres. We have found hSNM1B to interact with TRF2, a protein which functions in telomere protection and in an early response to ionizing radiation. Here we show that endogenous hSNM1B forms foci which colocalize at telomeres with TRF1 and TRF2. However, we observed that additional hSNM1B foci could be induced upon exposure to ionizing radiat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
38
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(45 citation statements)
references
References 32 publications
6
38
0
Order By: Relevance
“…Moreover, depletion of hSNM1B (siRNA) attenuated the autophosphorylation of the ATM-kinase at serine 1981 and the phosphorylation of several ATM target proteins, such as p53 and SMC1, in response to IR. 7 These results substantiated our earlier findings on hSNM1B function in the cellular response to DNA-damage. 6 Interestingly, similar to hSNM1B, TRF2 was also shown to have a function in the early response to DNA-damage: Bradshaw et al found that transiently expressed YFP-TRF2 accumulates at sites of photoinduced DNA damage.…”
Section: Introductionsupporting
confidence: 82%
See 2 more Smart Citations
“…Moreover, depletion of hSNM1B (siRNA) attenuated the autophosphorylation of the ATM-kinase at serine 1981 and the phosphorylation of several ATM target proteins, such as p53 and SMC1, in response to IR. 7 These results substantiated our earlier findings on hSNM1B function in the cellular response to DNA-damage. 6 Interestingly, similar to hSNM1B, TRF2 was also shown to have a function in the early response to DNA-damage: Bradshaw et al found that transiently expressed YFP-TRF2 accumulates at sites of photoinduced DNA damage.…”
Section: Introductionsupporting
confidence: 82%
“…The C-terminally tagged hSNM1B appeared in several bands, a previously observed characteristic which is most likely due to the use of alternative start codons. 7 Following the TAP procedure, the hSNM1B fusion protein was highly enriched while no signal was detectable from the controls (Fig. 1B).…”
Section: Hsc70mentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, in times of telomere crisis, or during the alternative lengthening of telomeres (ALT) pathway, phosphorylated Trf2 has been shown to localize to the telomere [70]. This discovery is not unexpected because many DNA damage-related proteins and telomeric proteins have been found to function within both contexts [69,71,72]. Apollo is also recruited to DSBs and interacts with …”
Section: Telomeresmentioning
confidence: 93%
“…Trf2 has also been recently implicated by various sources in the recognition and repair of DSBs in response to various forms of damaging radiation [68][69][70]. Trf2 is rapidly phosphorylated in response to DSBs.…”
Section: Telomeresmentioning
confidence: 99%